2(2x-8)=9(x+1)

Simple and best practice solution for 2(2x-8)=9(x+1) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2(2x-8)=9(x+1) equation:


Simplifying
2(2x + -8) = 9(x + 1)

Reorder the terms:
2(-8 + 2x) = 9(x + 1)
(-8 * 2 + 2x * 2) = 9(x + 1)
(-16 + 4x) = 9(x + 1)

Reorder the terms:
-16 + 4x = 9(1 + x)
-16 + 4x = (1 * 9 + x * 9)
-16 + 4x = (9 + 9x)

Solving
-16 + 4x = 9 + 9x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-9x' to each side of the equation.
-16 + 4x + -9x = 9 + 9x + -9x

Combine like terms: 4x + -9x = -5x
-16 + -5x = 9 + 9x + -9x

Combine like terms: 9x + -9x = 0
-16 + -5x = 9 + 0
-16 + -5x = 9

Add '16' to each side of the equation.
-16 + 16 + -5x = 9 + 16

Combine like terms: -16 + 16 = 0
0 + -5x = 9 + 16
-5x = 9 + 16

Combine like terms: 9 + 16 = 25
-5x = 25

Divide each side by '-5'.
x = -5

Simplifying
x = -5

See similar equations:

| -x-4x=15 | | 8(x+2)=(2x-1) | | 1s+7=90 | | x^3-3x^2-24x+12=0 | | 2(4n-8)-2n=10 | | 4p+4p=16 | | 7/2x=10 | | x+2+1=4 | | 78=5(2x+4)-8x | | z+6+4z-9+8u= | | -6t^2+72t+40=0 | | 3(x+8)=2(2x+14) | | 0=-3x^2-6x | | 6h-213=747 | | 256=7x-11 | | 2b=4b-6 | | 8+5x=2 | | X^5+16x^3+60x=0 | | 278=x^4 | | 20x+14y=17 | | 4a-10=-14 | | x/(x=2)=4/5 | | 3(x-0.80)=4x+4 | | -1=1x-2 | | 7x-101=61+13x | | 24000+0.09x= | | 4x+.5=3x-17 | | 4(m-b)=2+2(m-3) | | -125=-5d+10 | | 4x/4=-20/4 | | e-(-14)=21 | | 5=20/j |

Equations solver categories